ECG-Based Techniques to Optimize Peripherally Inserted Central Catheters: Rationale for Tip Positioning and Practical Use - Gullo, Giuseppe; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2022)
Intracavitary electrocardiography is an accurate guidance technique for central venous catheter tip location that is spreading widely among providers using non-radiologic means of locating peripherally inserted central catheters. The underlying technology is easy to understand, as it relies on the transmission of the electrocardiographic signal at the tip of the catheter and its use as an internal mobile electrode, allowing the system to identify the cavo-atrial junction through internal P-wave amplitude modulations. The gain in popularity of intracavitary electrography and its large diffusion have led manufacturers to offer various devices with heterogeneous properties, among which the clinician must choose. It is critically important to comprehend the underlying capacity of the system in centrally positioning the catheter. As important as good procedural technique is also the understanding of the advantages and limitations regarding electric signal transmission, hemostasis, device occlusion, and the composition of device material in direct relationship with the patient. Current perspectives on intracavitary electrocardiography will also be discussed strategically, to give the reader a global view of the management of electrocardiographically guided peripherally inserted central catheters outside a radiology department.